2010
DOI: 10.1002/arch.20379
|View full text |Cite
|
Sign up to set email alerts
|

Expression of pheromone biosynthesis activating neuropeptide and its receptor (PBANR) mRNA in adult female Spodoptera exigua (Lepidoptera: Noctuidae)

Abstract: The full-length cDNA of pheromone biosynthesis activating neuropeptide receptor (PBANR) was cloned from the beet armyworm, Spodoptera exigua (Hübner) (Lepidoptera: Noctuidae); it included an open reading frame of 1,053 bp encoding 350 amino acids. The PBANR of S. exigua (SePBANR) was structurally characteristic of G protein-coupled receptor and its amino acid sequence shared 98% identity with the PBANR of Spodoptera littoralis. Both pheromone biosynthesis activating neuropeptide (PBAN) and PBANR mRNA abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 43 publications
(60 reference statements)
3
24
0
Order By: Relevance
“…was detected from neuronal tissues such as brain, ventral nerve cord, thoracic ganglion as well as male aedaegus, homologous to female pheromone gland (Rafaeli et al, 2007). PBANr expression from Spodoptera exigua was found in suboesophageal ganglion, ventral nerve cord, pheromone gland, and ovary (Cheng et al, 2010). Relative PBANr expression level of neuronal tissue was much lower than that of pheromone gland in Helicoverpa spp.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…was detected from neuronal tissues such as brain, ventral nerve cord, thoracic ganglion as well as male aedaegus, homologous to female pheromone gland (Rafaeli et al, 2007). PBANr expression from Spodoptera exigua was found in suboesophageal ganglion, ventral nerve cord, pheromone gland, and ovary (Cheng et al, 2010). Relative PBANr expression level of neuronal tissue was much lower than that of pheromone gland in Helicoverpa spp.…”
Section: Discussionmentioning
confidence: 94%
“…However, other reports suggest that other neuronal tissue also can be the target of PBAN (Rafaeli et al, 2007;Cheng et al, 2010). PBANr transcript from female Helicoverpa spp.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The reference gene of β-actin was used as an endogenous control when quantification of target genes was determined. This gene is an appropriate control in this insect during this wide developmental window as determined in our previous studies (Tian et al 2009;Cheng et al 2010). The average concentration across replicates was obtained from the standard curves and the relative expression ratio of each target gene was calculated according to protocols established by the manufacturer (ABI Prism 7700 Sequence Detection System).…”
Section: Data Collection and Statistical Analysismentioning
confidence: 99%
“…The PBAN receptor (PBANR) was first cloned from H. zea (20) as an ortholog of the vertebrate neuromedin U receptor (NMUR) (21)(22)(23)(24), which recognizes peptides with a C-terminal FRPRN-NH 2 motif such as neuromedin U (NMU) and neuromedin S (25,26). Since then, PBANRs from B. mori (27), Heliothis virescens (28), Manduca sexta (GenBank TM accession numbers FJ240221 to FJ240224), 5 Plutella xylostella (29), Helicoverpa armigera (30), Spodoptera littoralis (31), Spotoptera exigua (32), Pseudaletia separata (33), and Ostrinia nubilalis (34) have been identified. Functional analyses have shown that PBANR activation triggers an influx of extracellular Ca 2ϩ in isolated B. mori pheromone glands (35) as well as insect cells transiently expressing PBANR (20,27).…”
mentioning
confidence: 99%